Biologia reprodutiva de Amphisbaena silvestrii (Boulenger, 1902) (Squamata, Amphisbaenidae) da região do Vale de São Domingos, Mato Grosso, Brasil - Calcanhoto, Karla Katherine Nascimento (2013)
Amphisbaenians are reptiles fossorial and have their biology poorly known. Most reports on reproduction in amphisbaenids is restricted to the description of the mode of reproduction. The aim of this study was to characterize the morphological and morphometric variations Amphisbaena silvestrii using histology of the gonads and gametes of conducting channels , estimating fecundity , maturity , gender dimorphism and sintopy gonad. For that specimens from the Zoological Collection of the Federal University of Mato Grosso were analyzed. Measures of the testes, vas deferens, follicles and oviducts were performed. All females showed primary follicles. The males showed variation in the extent of the testes and vas deferens showing variations in gametogenic activity. Females showed greater snout-vent length and number of lateral rings. The number of eggs laid per female probably varies between 1 and 3. The maturity in females is probably achieved between 122 and 173 mm of CRC in males and between 118 and 185 mm CRC. There aren’t differences in the production of eggs or follicles by right and left ovaries. The gonads are more right side than the left cranial side. The reproductive cycle of males and females is the continuous and synchronous type, mature cells of spermatogenesis (sperm) were observed filling all the seminiferous tubules, sperm always present in light of the vas deferens, and the females showed active glands during all sampling periods.